Boron-rich, cytocompatible block copolymer nanoparticles by polymerization-induced self-assembly. Issue 1 (14th August 2020) - Huang, Lin-Chiang Sherlock; Le, Dao; Hsiao, I-Lun; Fritsch-Decker, Susanne; Hald, Christian; Huang, Su-Ching; Chen, Jen-Kun; Hwu, Jih Ru; Weiss, Carsten; Hsu, Min-Hua; Delaittre, Guillaume
Abstract : A new methacrylic boronate ester is synthesized and exploited to produce biocompatible nanoparticles with a boron-rich core by PISA. Abstract : Core–shell nanoparticles (NPs) with a boron-rich core were synthesized by RAFT-mediated polymerization-induced self-assembly using a new methacrylic boronate ester monomer. Under specific conditions, sub-100 nm spherical NPs could be obtained at high conversions by either emulsion or dispersion RAFT polymerization using poly(oligo(ethylene glycol) methacrylate) (POEGMA) dithiobenozate-based chain transfer agents. Phenylboronic acid surface-functionalized NPs were obtained using a telechelic POEGMA. Primary data on biocompatibility is provided and suggests suitability as boron delivery agent for boron neutron capture therapy.